Philippine travel phrase book English-Tagalog-Cebuano - Latorre, Luis Esteban A. (Tahanan Pacific, 1993)
This is a phrasebook for English and two of the most widely spoken native languages in the Philippines, Tagalog and Cebuano. It is divided into a range of situations, from one's arrival at the airport to what one should say in an emergency. It is organized into three columns for easy access. It provides an overview of Philippine history and culture and simple rules for Tagalog and Cebuano pronunciation. It also has a reference section, maps, glossary and an index. Intended audience is foreigners and non-native speakers.